Investor Demand for Internal Control Audits of Large U.S. Companies: Evidence from a Regulatory Exemption for M&A Transactions - Carnes, Robert R.; Christensen, Dane M.; Lamoreaux, Phillip T. (The Accounting Review, 2019)
ABSTRACT Because internal control audits never existed before the passage of the Sarbanes-Oxley Act (SOX), and these audits simultaneously became mandatory for all U.S. accelerated filer companies, it has been difficult to assess the extent of investor demand for these audits. To understand whether investors demand internal control audits for these large companies, we exploit a regulatory exemption that permits companies to exclude acquired operations from an internal control audit. Using this voluntary setting, we find that investors react negatively if a company excludes acquired operations from their internal control audit. This negative reaction is larger when more of the company's operations are excluded from audit and when there is greater information uncertainty. Further, companies that exclude acquired operations from internal control audits are more likely to have a subsequent restatement. Collectively, these findings are consistent with investors perceiving value in (i.e., demanding) internal control audits for large U.S. public companies. JEL Classifications: M41; M42.